Talent Management in the Knowledge Economy:Strategies for Attracting and Retaining Top Talent - Rusbiansyah Perdana Kusuma; Bambang Mardi Sentosa (AKADEMI TEKNIK ADI KARYA, 2024)
In the era of knowledge-based economy, talent management is a key element in improving organizational competitiveness. This research aims to identify effective strategies in attracting and retaining the best talent amid dynamic changes in the labor market. Through a qualitative approach and case studies on leading companies, this study explores the key factors that influence talent's decision to join and stay in an organization. The results show that a work environment that supports innovation, sustainable career development, and competitive compensation policies are the main factors in talent management. In addition, the company's ability to build an inclusive and collaboration-based work culture has also proven to play an important role in retaining high-quality talent. These findings provide guidance for organizations to design more effective talent management strategies in the context of a knowledge-based economy.